2018
DOI: 10.1111/aor.13322
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Stimulation of Whole Heart Constructs in an 8‐Pole Electrical Field

Abstract: Within the field of whole organ engineering and especially for whole heart constructs (WHC) one of many challenges still lies in overcoming technical obstacles to transfer processing and stimulation concepts that have already gained acceptance in 2D and 3D myocardial models (1,2). By their pioneering work, Ott and colleagues have shown the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Combinations of both techniques have also been described . Whole‐heart recellularization in the rat model is commonly performed using rNCs and RAECs . Various research groups have observed electrical signalling and corresponding contraction in vitro , where recellularized hearts were maintained for up to 30 days .…”
Section: Heartmentioning
confidence: 99%
See 3 more Smart Citations
“…Combinations of both techniques have also been described . Whole‐heart recellularization in the rat model is commonly performed using rNCs and RAECs . Various research groups have observed electrical signalling and corresponding contraction in vitro , where recellularized hearts were maintained for up to 30 days .…”
Section: Heartmentioning
confidence: 99%
“…On the other hand, tissue engineering of the heart requires electrical and biomechanical stimulation, such as the system built by Hülsmann et al . . In the tissue engineering of organs such as the liver, monitoring of the levels of albumin and coagulation factors is of crucial importance.…”
Section: Bioreactors For De‐ and Recellularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The RCNN model is a promising decoder of EMG and the sensor fusion can increase the accuracy and robustness of the myoelectric control system. Jörn Hülsmann et al 86 of the Heinrich Heine University, Duesseldorf, Germany, reported on the impact of threedimensional electrophysiological (EP) stimulation of tissue-engineered whole heart constructs (WHC) in a custom made eight-pole electrical field stimulation system by short model cultivations with neonatal rat cardiomyocytes (CM). Strong reduction of voltage signals by the decellularized extracellular matrix (ECM) component of WHC was observed.…”
Section: Stimulation and Neuromuscular Supportmentioning
confidence: 99%